Antidepressant efficacy is correlated with plasma levels: mega-analysis and further evidence - Cellini, Lorenzo; De Donatis, Domenico; Zernig, Gerald; De Ronchi, Diana; Giupponi, Giancarlo; Serretti, Alessandro; Hart, Xenia Marlene; Conca, Andreas; Florio, Vincenzo (International clinical psychopharmacology, 2022)
The debate around optimal target dose for first-line antidepressants (ADs) is still ongoing. Along this line, therapeutic drug monitoring (TDM) represents one of the most promising tools to improve clinical outcome. Nevertheless, a few data exist regarding the concentration-effect relationship of first-line ADs which limits TDM implementation in routine clinical practice. We conducted the first patient-level concentration-response mega-analysis including data acquired by us previously and explored the concentration dependency of first-line AD (206 subjects). Further, new data on mirtazapine are reported (18 subjects). Hamilton Depression Rating Scale-21 administered at baseline, at month 1 and month 3 was used as the measure of efficacy to assess antidepressant response (AR). When pooling all four first-line ADs together, normalized plasma levels and AR significantly fit a bell-shaped quadratic function with a progressive increase of AR up to around the upper normalized limit of the therapeutic reference range with a decrease of AR at higher serum levels. Our results complement the available evidence on the issue and the recent insights gained from dose-response studies. A concentration-dependent clinical efficacy, such as previously demonstrated for tricyclic compounds, also emerge for first-line ADs. Our study supports a role for TDM as a tool to optimize AD treatment to obtain maximum benefit.
Gesehen am 17.09.2024
Vor- und Nachname von Xenia Hart sind in der Verfasserangabe fälschlich vertauscht worden